Unspoken Tension: Grammar in Discourse as a Key to Reading Hemingway’s “The Killers” - Chatarini Septi Ngudi Lestari; Suprihatien; Urip Zaenal Fanani (Journal of Applied Studies in Language, 2026)
This study examines Ernest Hemingway’s short story “The Killers” through the lens of Grammar in Discourse, focusing on how grammatical structures function at both the sentence and discourse level as resources for meaning-making in interaction and narrative. The aims are to examine how Hemingway’s grammar operates at the discourse level to shape interactional dynamics and narrative tension, to fill a scholarly gap by providing a systematic analysis of his grammar within this framework, and to highlight the pedagogical potential of using Hemingway’s text in teaching grammar. This study employs a qualitative descriptive method, analysing excerpts with attention to tense, modality, deixis, ellipsis, repetition, and voice. The analysis shows that Hemingway’s minimalist grammar serves as a stylistic device to heighten tension, realism, and ambiguity. The consistent use of past simple and ellipses in dialogue builds a sense of immediacy and sounds natural. Modal expressions and imperatives emphasize the unequal power dynamic between the gangsters and the victims. Deictic expressions and vague references add to the uncertainty, supporting Hemingway’s iceberg theory of leaving meaning beneath the surface. Pedagogically, the study highlights the potential of integrating literary texts into the teaching of Grammar in Discourse, encouraging learners to see grammar as a resource for constructing meaning, negotiating power, and interpreting stylistic effects.